Trend Seminar Online Kewirausahaan; Kapabilitas Daya Serap Pengetahuan sebagai Mediasi Knowledge Sharing Anggota UKM dalam Menciptakan Inovasi UKM di Sidoarjo - Ayu Lucy Larassaty; Muhafidhah Novie; Virawati Tanaya; Erwinda Eka Prastyawati (Journal of Research and Technology, 2022)
SMEs compete in the business arena in terms of managerial, process and product. The competitive advantage of SMEs depends on the ability to assimilate a variety of knowledge. The aim of the researcher is to find out the Trend of Entrepreneurship Online Seminar; knowledge absorption capability as a mediation for knowledge sharing of SME members in creating SME innovation in Sidoarjo. What is the form of implementation? The research method adopted a mix method approach with qualitative methods (FGD) and quantitative survey methods using questionnaires and analysed using the GSCA application. The results of the first analysis explain that absorption capability is a liaison for knowledge sharing in creating innovation for SMEs in Sidoarjo, while the results of the second analysis using FGD explain that not all SMEs implement the form of knowledge sharing and do not pay attention to the absorption capability. This is done after attending an online entrepreneurship seminar to create innovation because the seminars that are attended are sometimes not on target and the needs of SMEs.